The Correlation of Restless Leg Syndrome with Endometriosis: A Cross-Sectional Study - Mufeed Taha (Al-Anbar Medical Journal)
Background: Restless leg syndrome (RLS) is a common neurological disorder, but its correlation with endometriosis remains unclear.Objectives: To evaluate the correlation of RLS with endometriosis.Methods: A cross-sectional study included 155 patients who were diagnosed with RLS at the Neurology Department, Azadi Teaching Hospital, Kirkuk, Iraq. The study started on 1st June 2020 and ended on 1st March 2023. RLS was diagnosed using the criteria established by the International Restless Leg Syndrome Study Group (IRLSSG). The researchers questioned the patients about their history of endometriosis. Then categorized into two groups. The first group consisted of 72 cases with surgically confirmed endometriosis, whose severity was determined by the Gynecologists following the guidelines of the revised American Society of Reproductive Medicine (rASRM). The remaining 83 cases formed a group comprising individuals with RLS without endometriosis. We collected data from each participant about their age, marital status, smoking habit, and body mass index (BMI).Results: One hundered fifty five patients with a mean age of 29.19 ± 6.12 years were diagnosed with RLS. There was a statistically significant difference (P-value = 0.029) between the RLS and the age of the patients with endometriosis compared to those without endometriosis. However, there were no significant statistical differences (P-value > 0.05) in marital status, smoking habits, or BMI between the two groups. In terms of RLS severity ratings, patients with endometriosis tended to have more severe rating scales compared to those without this condition. Additionally, a Pearson's correlation test showed a strong positive correlation, between IRLSSG and rASRAM scores (P-value = 0.0001, r = 0.7).Conclusion: RLS was strongly and positively correlated with endometriosis. However, the exact cause and nature of this correlation remained obscure.